The risks of a range of maternal pregnancy choices, expressed as "baby micromorts" (risk of death per million births). (August 2020) - Hickson, Charlotte; Hoskins, Felicity; Ogollah, Reuben; Walker, Kate F.; Thornton, Jim G.
Abstract: Objective: To present the risks of baby death from various maternal choices on a common scale. Design: Review of published data. Methods: Mortality calculated as the attributable risk per activity, expressed in "baby micromorts", the number of one in a million chances of the baby dying. Results: Amniocentesis and chorionic villous sampling carry procedure related risks of 9142 (-600 to 19, 000) and 37, 902 (23, 302 to 52, 502) micromorts respectively. Smoking carries a risk of 0.21 micromorts per cigarette or 300 micromorts for a woman smoking 5/day throughout pregnancy. Drinking a unit of alcohol in the first trimester carries a risk of 400 micromorts via miscarriage or 19, 200 micromorts for a woman drinking 4 units/week in the first trimester. The risk per unit due to stillbirth is only about 19 or 3, 710 micromorts when drinking 5 units/week throughout pregnancy. Cocaine use carries a risk of about 45 micromorts per single use; 3, 630 micromorts using cocaine twice/week during pregnancy. For low risk women in the UK, planned first birth at home carries an additional 843 (−200 to 2620) micromorts compared with in hospital, and planned vaginal breech birth an additional 5870 (-4400 to 18, 500), compared with planned caesarean. The risk of delaying conception by a year varies by age group. For women aged 35–39 the risk increases by 220 (−430 to 870) micromorts each year versus 600 (−800 to 2000) micromorts for women aged over 40. Compared with the above, the risk from the mother eating a serving of unpasteurised cheese, is negligible at 0.00026 micromorts. Conclusions: This way of expressing risk may help put choices which pregnant women make into perspective, although it needs evaluating in well conducted experimental studies.